Outcomes of Tuberculous Meningitis Patients with Hydrocephalus with or without Cerebrospinal Fluid Diversion - Nabila Chantikarizky Hasanah; Akhmad Imron; Ahmad Rizal Ganiem (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Hydrocephalus is a common complication in tuberculous meningitis patients and is a poor predictor with high mortality and morbidity rates. Therefore, early diagnosis, detection, and treatment of hydrocephalus are important. Cerebrospinal fluid diversion is the process used to drain accumulated fluid in the brain and spinal cord. This study aimed to explore the outcome of tuberculous meningitis patients with hydrocephalus who underwent cerebrospinal fluid diversion and who did not.Methods: This was a retrospective cross-sectional descriptive study, including tuberculosis meningitis patients with hydrocephalus, admitted at the Department of Neurology Dr. Hasan Sadikin Bandung General Hospital during the period 2018. Functional outcomes were grouped based on the Glasgow Outcome Scale.Results: Of the 55 patients, only 14 (25.5%) underwent cerebrospinal fluid diversion. The outcome of patients with cerebrospinal fluid diversion was 8 of 14 good, 1 of 14 poor, and 5 of 14 died. The outcome of patients without cerebrospinal fluid diversion was 13 of 41 good, 2 of 41 poor, and 26 of 41 died. Most tuberculous meningitis patients with hydrocephalus, with or without the cerebrospinal fluid diversion procedure were at an advanced stage with a high mortality rate. Conclusion: The proportion of good functional outcomes in patients with cerebrospinal fluid diversion is higher than in patients without the cerebrospinal fluid diversion.